Kandidat Vaksin Potensial Streptococcus agalactiae untuk Pencegahan Penyakit Streptococcosis pada Ikan Nila (Oreochromis niloticus) (POTENTIAL VACCINE CANDIDATE OF STREPTOCOCCUS AGALACTIAE FOR PREVENT STREPCOCOCOSIS ON NILA TILAPIA (OREOCHROMIS NILOTICUS) - Hardi, Esti Handayani; ., Sukenda; Harris, Enang; Lusiastuti, Angela Mariana (Jurnal Veteriner; Vol 14 No 4 (2013), 2013)
The effectiveness of Streptococcus agalactiae vaccine in tilapia (Oreochromis niloticus) was evaluatedfor prevention of streptococcal disease. The vaccine was prepared using formalin-killed whole cell andconcentrated extracellular products/ECP (62.3 and 55.8 kDa) of â-haemolityc isolate and 62.3; 55,8 and51.8 kDa protein of  non-haemolityc ECP of S. agalactiae.  Vaccination and challenged (103 colony-formingunits (CFU)/fish of â-haemolityc and 105 CFU/fish of non-haemolityc S. agalactiae) trial was conducted byintraperitonial (IP) injection into fish with average body weight of 15 g.  Fish were vaccinated with wholecell, ECP and mixed (whole cell and ECP) vaccine.  Tilapia vaccinated with whole cell of â-haemolitycisolate had a relative percent survival (RPS) rates higher than those of ECP â-haemolityc vaccine. However,fish  vaccinated with mixed (whole cell and ECP) of â-haemolityc has a better protection rates as comparedto those of two type of S. agalactie infection. Whereas those vaccinated with mixed (whole cell non-haemolitycand ECP of â-haemolityc) vaccine has protection rate of 79% from â-haemolityc and 42% from non-haemolitycinfection.  Tilapia vaccinated with whole cell of non-haemolityc was only able to protect fish from non-haemolityc infection and was unable to protect fish from other types.  Tilapia vaccinated with ECP non-haemolityc had a worse RPS than others vaccines in which mix whole cell and ECP vaccine of non-haemolitychad a protection 50-56% from  S. agalactiae infection. Whereas vaccinated with mixed (whole cell â-haemolityc and ECP of non-haemolityc) vaccine showed a better to protect from â-haemolityc than non-haemolityc infection.  It showed thatvaccination with mixed (whole-cell and extracellular product)  vaccineof S. agalactiae â-haemolityc  was more effective to protect tilapia against Streptococcosis.
Keywords: S. agalactiae, ECP, whole cell, vaccination